THE EXCLUSIVITY OF FARMERS IN THE OIL PALM INDUSTRY - Zamzam Muhammad Fuad (Jurnal Politik Profetik, 2022)
Amin Tohari. Politik Sawit: Akses, Identitas dan Perubahan. Makassar: Carabaca, 2021. Pp: xx+196. ISBN: 978-623-95699-9-0. This article is a review of a book entitled Politik Sawit: Akses, Identitas dan Perubahan, written by Amin Tohari. The book on Politik Sawit is a good contribution to the development of political science in Indonesia. This book does not only look at oil palm in terms of economic profit and loss. Palm oil is also not sufficiently understood as a source of welfare or a contributor to the country's foreign exchange. Moreover, the book Politik Sawit succeeded in continuing an agrarian political discourse that made palm oil a battlefield of interest between various actors. The book on Politik Sawit shows that, once again, farmers are the target of exploitation from the agrarian system which is pro-business entrepreneurs with large capital. Therefore, this book can be used as a reference for academics who are pursuing the field of agrarian political studies. In addition, policymakers can also use this book to formulate fair palm oil industry policies for oil palm smallholders.